2023
DOI: 10.3389/fncel.2023.1084769
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Rho and Rab family of small GTPases in neurodegenerative disorders

Abstract: Neurodegeneration is associated with defects in cytoskeletal dynamics and dysfunctions of the vesicular trafficking and sorting systems. In the last few decades, studies have demonstrated that the key regulators of cytoskeletal dynamics are proteins from the Rho family GTPases, meanwhile, the central hub for vesicle sorting and transport between target membranes is the Rab family of GTPases. In this regard, the role of Rho and Rab GTPases in the induction and maintenance of distinct functional and morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 160 publications
0
2
0
Order By: Relevance
“…For example, large omics data are now available that demonstrate many gene dysregulations are spatially affected and cell/tissue selective. In AD mouse models, we showed that small Rho GTPase signaling is even dysregulated at both spatial and planar levels in brain (8). Therefore, homeostatic targeting may have profound benefits in addition to the traditional and simple inhibitory or stimulatory treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, large omics data are now available that demonstrate many gene dysregulations are spatially affected and cell/tissue selective. In AD mouse models, we showed that small Rho GTPase signaling is even dysregulated at both spatial and planar levels in brain (8). Therefore, homeostatic targeting may have profound benefits in addition to the traditional and simple inhibitory or stimulatory treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Ras superfamily proteins are small GTPases that act as molecular switches and regulate a myriad of essential cellular functions in proliferation, vesicular transport, cell motility, and others ( 8, 9 ). Cdc42, a classical member of the Rho GTPase subfamily, is an important regulator of many biological processes ( 1012 ).…”
Section: Enabling Systemic Identification Of Hms On Cdc42-itsn Signalingmentioning
confidence: 99%